Aplikasi Kaidah Lâ Dharara Wa Lâ Dhirâr Dalam Hukum Ekonomi Syariah - Agus Putra, Panji Adam (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
There are many legal issues that need to be resolved and answers found, one of which is in the field of muamalah and economic transactions. The scholars have carried out ijtihad in order to determine the legal status of an issue. In addition to the science of ushul fiqh, the science of fiqh rules is a device and tool used by Islamic jurists in carrying out ijtihad. With this rule of fiqh, it will make it easier for the scholars to carry out the process of discovering and establishing law. One of the principles of fiqh that is widely used by scholars in formulating laws is the principle of asahi which reads Lâ Dharar wa lâ Dhirâr, which means that one must not harm oneself and one cannot harm others. This rule has several branch rules. The purpose of this study is to explain the meaning of the principle of principle regarding the prohibition of doing harm and examine its application in sharia economic law activities. The results of the study show that the meaning of the Lâ Dharar wa lâ Dhirâr rule is the prohibition of harming oneself or others, both materially and spiritually. This rule has ten branch rules that can be applied in sharia economic law activities. Keywords: Jurisprudence Rules, Keudaratan, Dharar wa Dhirâr, Sharia Economic Law